2007
DOI: 10.1007/s11661-007-9407-z
|View full text |Cite
|
Sign up to set email alerts
|

Transmission Electron Microscopy Study on the Grain Boundary Precipitation of an Fe-Ni-Mn Maraging Steel

Abstract: Transmission electron microscopy was used to study grain boundary precipitation of an Fe-10Ni-7Mn (wt pct) maraging steel during isothermal aging at 753 K. Precipitation of a facecentered tetragonal (fct) h-NiMn phase in association with solute-depleted precipitate free zone (PFZ) was found at prior austenite grain boundaries. Precipitation-induced puckering of grain boundaries in the early stages of aging initiates grain boundary displacement, creating PFZs behind the displaced grain boundary. Further grain b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Hossein Nedjad et al [9] reported preliminarily an improvement in the tensile properties of an Fe-10Ni-7Mn maraging steel after cold rolling for 85% and subsequent aging at 753 K. Nevertheless, effect of cold rolling for a wide range of thickness reduction in combination with isothermal aging treatment needs to be more clarified. Further, it has been demonstrated that cold rolling and aging of the Fe-Ni-Mn steel realizes ultrafine grain formation [10]. Therefore, the aim of this paper is to determine the tensile properties and microstructure evolution of an Fe-10Ni-7Mn steel after sever plastic deformation by cold rolling and ECAP processes.…”
Section: Introductionmentioning
confidence: 99%
“…Hossein Nedjad et al [9] reported preliminarily an improvement in the tensile properties of an Fe-10Ni-7Mn maraging steel after cold rolling for 85% and subsequent aging at 753 K. Nevertheless, effect of cold rolling for a wide range of thickness reduction in combination with isothermal aging treatment needs to be more clarified. Further, it has been demonstrated that cold rolling and aging of the Fe-Ni-Mn steel realizes ultrafine grain formation [10]. Therefore, the aim of this paper is to determine the tensile properties and microstructure evolution of an Fe-10Ni-7Mn steel after sever plastic deformation by cold rolling and ECAP processes.…”
Section: Introductionmentioning
confidence: 99%
“…The Fe-10Ni-7Mn (wt.%) low carbon martensitic steel is classified as an ultra-high strength steel which exhibits adequate ductility in the solution annealed (SA) condition. However, this excellent age-hardenable steel suffers from post-aging intergranular embrittlement along prior austenite grain boundaries [1,2]. Recent efforts have focused on the effects of adding alloying elements [3,4], intercritical annealing [5,6] and also employing various severe plastic deformation methods to improve the alloy ductility after aging [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…As the ageing temperature increases to 600 °C (see Figure 1d), the dimensions of Ni 3 Ti precipitates become larger, and the length of Ni 3 Ti is 78.8 ± 10.2 nm. [ 12 ] To some degree, it can be detected that there is coarsening of boundaries, and the boundaries coarsening would result in the generation of precipitation‐free zones (PFZs) at the boundaries, [ 32,33 ] as shown in Figure 1d. As the ageing temperature further upgrades to 630 °C, it can be observed from Figure 1e and f that the sizes of Ni 3 Ti, boundaries, and PFZs would further improve, and the distribution of Ni 3 Ti becomes sparse.…”
Section: Resultsmentioning
confidence: 99%
“…Chemical compositions of the experimental maraging steel (wt%). [12] Ti Cr (PFZs) at the boundaries, [32,33] as shown in Figure 1d. As the ageing temperature further upgrades to 630 °C, it can be observed from Figure 1e and f that the sizes of Ni 3 Ti, boundaries, and PFZs would further improve, and the distribution of Ni 3 Ti becomes sparse.…”
Section: Microstructuresmentioning
confidence: 99%